Comprehensive Physiology 2014
DOI: 10.1002/cphy.c140023
|View full text |Cite
|
Sign up to set email alerts
|

Organic Anion Uptake by Hepatocytes

Abstract: Many of the compounds taken up by the liver are organic anions that circulate tightly bound to protein carriers such as albumin. The fenestrated sinusoidal endothelium of the liver permits these compounds to have access to hepatocytes. Studies to characterize hepatic uptake of organic anions through kinetic analyses, suggested that it was carrier-mediated. Attempts to identify specific transporters by biochemical approaches were largely unsuccessful and were replaced by studies that utilized expression cloning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 217 publications
(309 reference statements)
1
24
0
Order By: Relevance
“…P revious studies showed that the hepatocyte efficiently eliminates organic anions from the circulation with single-pass extraction as high as ≥50%. (1) Pharmacokinetic studies were consistent with carrier mediation, (2,3) and subsequent functional cloning experiments identified a transport protein, initially named organic anion transporting polypeptide (OATP). (4,5) This 75-kDa glycoprotein has 12 transmembrane domains (6) and is sufficient to mediate ligand transport when transfected into various cell lines.…”
Section: Rat Organic Anion Transport Protein 1a1 Interacts Directly Wmentioning
confidence: 90%
See 4 more Smart Citations
“…P revious studies showed that the hepatocyte efficiently eliminates organic anions from the circulation with single-pass extraction as high as ≥50%. (1) Pharmacokinetic studies were consistent with carrier mediation, (2,3) and subsequent functional cloning experiments identified a transport protein, initially named organic anion transporting polypeptide (OATP). (4,5) This 75-kDa glycoprotein has 12 transmembrane domains (6) and is sufficient to mediate ligand transport when transfected into various cell lines.…”
Section: Rat Organic Anion Transport Protein 1a1 Interacts Directly Wmentioning
confidence: 90%
“…Pijun Wang, 1 Wen-Jun Wang, 1,2 Jo Choi-Nurvitadhi, 1,2 Yaniuska Lescaille, 1,3 John W. Murray, 1,2 and Allan W. Wolkoff [1][2][3] Organic anion transport proteins (OATPs) on the basolateral surface of hepatocytes mediate uptake of a number of drugs and endogenous compounds. Previous studies showed that rat OATP1A1 (rOATP1A1) has a postsynaptic density protein, drosophila disc large tumor suppressor, zonula occludens-1 protein (PDZ) consensus binding motif at its C-terminus and binds to PDZ domain containing 1 (PDZK1), which is required for its cell-surface localization.…”
Section: Rat Organic Anion Transport Protein 1a1 Interacts Directly Wmentioning
confidence: 99%
See 3 more Smart Citations